Pengaruh Lama Fermentasi Kimchi terhadap Karakteristik Sensori berdasarkan Selera Orang Indonesia - Firanisa A, Raysyiva; Yumna, Arkis; Olland DM, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Chicory is a vegetable that has a highwater content, so it does not have a long shelf life. Therefore, to extend the shelf life, further processing is needed, namely preservation. The preservation method commonly used for vegetable commodities is fermentation. Kimchi is a product preserved using the fermentation method. Kimchi fermentation is carried out spontaneously or in other words, no starter is added to the process. This research was carried out using an experimental method and for data collection the method used was hedonic testing or the liking test of 5 panelists using sensory parameters, namely color, taste, aroma and texture. According to the data, of these four aspects, the fermentation time that best suits Indonesian tastes is on day 4 which shows significant results on sensory characteristics.